2008
DOI: 10.1080/15572536.2008.11832493
|View full text |Cite
|
Sign up to set email alerts
|

Chemotaxis of the amphibian pathogenBatrachochytrium dendrobatidisand its response to a variety of attractants

Abstract: Batrachochytrium dendrobatidis is a fungal pathogen of amphibians that is increasingly implicated as a major cause of large-scale mortalities of amphibian species worldwide. Previous studies indicate that motile zoospores of B. dendrobatidis colonize the keratinized tissues of susceptible amphibians. Infections spread to adults and cause destruction of epidermal tissue. In an effort to understand how the chytrid cues into its host we developed an assay to study chemotaxis in the fungus. Here we show that zoosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(19 citation statements)
references
References 24 publications
0
19
0
Order By: Relevance
“…A lowered population density, as observed in the low N:P treatment, may have resulted in an increased light availability due to reduced self-shading. Earlier studies have indicated that zoospores may find their host using chemical cues that are related to photosynthetic activity, since zoospores are generally attracted to carbohydrates, polysaccharides, proteins and amino acids (Muehlstein et al, 1988; Donaldson and Deacon, 1993; Moss et al, 2008). Some studies, however, also reported attachment of zoospores to new hosts during dark conditions (Barr and Hickman, 1967).…”
Section: Discussionmentioning
confidence: 99%
“…A lowered population density, as observed in the low N:P treatment, may have resulted in an increased light availability due to reduced self-shading. Earlier studies have indicated that zoospores may find their host using chemical cues that are related to photosynthetic activity, since zoospores are generally attracted to carbohydrates, polysaccharides, proteins and amino acids (Muehlstein et al, 1988; Donaldson and Deacon, 1993; Moss et al, 2008). Some studies, however, also reported attachment of zoospores to new hosts during dark conditions (Barr and Hickman, 1967).…”
Section: Discussionmentioning
confidence: 99%
“…The effect of season may be driven by various factors; the temperatures during the spring months are within the range for optimal Bd growth [52], and Bd -infected animals are returning to breeding sites, shedding zoospores into the water and transmitting the infection to each other as they congregate. Alternatively or additionally, springtime increases in host abundance may elicit a chemotactic response from free-living Bd [91], which could contribute to an observed increase in the zoospore density in water.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the rate at which the fungus grows can determine the abundance of zoospores in the environment and therefore the likelihood of host exposure and infection [44]. The motility of zoospores will also affect the likelihood of exposure events as actively dispersing keratinophyllic zoospores would have a higher probability of encountering new hosts [47].…”
Section: Discussionmentioning
confidence: 99%